Positifikasi Isbat Talak dalam Perlindungan Hak Perempuan: Analisis Komparatif Hukum Mesir dan Maroko Perspektif Maqashid Syariah - Jamili, Faizah; Elimartati, Elimartati; Atsani, Ulya; Zulkifli, Zulkifli; Nofialdi, Nofialdi; Yunarti, Sri (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
Marriage in Islam is viewed as a sacred and strong bond, or mitsaqan ghalidzan. However, in Indonesian social reality, the practice of divorce under the hand or outside the courts is still common. This phenomenon triggers serious legal problems due to the legal vacuum regarding the isbat talak regulation in the national legal system. Without formal state approval, the legal status of wives and children is often neglected, resulting in the loss of post-divorce rights such as custody, maintenance, and access to civil registration. This research uses a normative juridical approach through a comparative study of family law in Indonesia with regulations in Egypt and Morocco. Theoretically, the analysis is based on legal theory as a means of societal renewal and the theory of legal positivization to transform religious norms into written positive law. Furthermore, the Maqasid Syari'ah perspective is used to ensure that each proposed regulation aligns with the goal of protecting the interests of religion, life, descendants, intellect, and property for Muslim families. The research findings indicate that Indonesia urgently needs to strengthen the regulation of divorce confirmation (isbat talak) to bridge the dualism between the religious validity of divorce and the legality of state administration. A comparison with Egypt and Morocco found that integrating stricter regulations regarding divorce ratification can provide greater legal certainty for the public. This strengthening measure is considered a strategic solution to create legal order and guarantee the constitutional rights of family members, who have been vulnerable to uncertainty. In conclusion, strengthening the regulation of divorce confirmation (isbat talak) through positive law is an urgent need to achieve legal justice for families in Indonesia. Transforming Islamic legal norms into national legislation will ensure that legal protection for wives and children is no longer partial, but comprehensive and formally binding. Thus, the purpose of marriage, which is to create welfare, can be maintained even if the union ends in divorce.